A thermodynamic approach to the stabilization of tubular reactors. (December 2021) - Zhou, Weijun; Hamroun, Boussad; Le Gorrec, Yann; Couenne, Françoise
Abstract: This paper deals with the stabilization of a non isothermal tubular reactor in which convection, diffusion and chemical reaction occur. The tubular reactor is modelled by a set of non-linear partial differential equations and the distributed jacket temperature is used as control input. Two stabilizing control laws are derived using the thermodynamic availability function as a Lyapunov function. It is shown how the closed loop performances, in terms of settling time and input control amplitude can be improved by modifying the availability function. Simulation results show the effectiveness of the proposed state feedback controls. Highlights: Non-linear control laws to the stabilization of tubular reactors are designed Availability function is used as Lyapunov function from thermodynamic considerations. Reduced availability function is proposed as Lyapunov function for stabilization. Simulation results show the effectiveness of the proposed state feedback controls.